2021
DOI: 10.1080/08856257.2021.1872850
|View full text |Cite
|
Sign up to set email alerts
|

No nursery ‘til school – the transition to primary school without institutional transition support due to the COVID-19 shutdown in Germany

Abstract: The early educational support of basic school skills during nursery can have a positive impact on a successful transition into primary school and future school success and achievement -especially for in this context low-performing children. Therefore, most German nurseries developed additional concepts to support the acquisition of basic school skills during the last year of nursery. However, due to the COVID-19 shutdown face-to-face support for pre-schoolers was closed down. This study attempts to examine how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, students' feeling of fear was not strongly observed in this study. On the contrary, [19] found that kindergarten students with special needs view their school future with fear. This difference in the results may stem from the difference in the students' age and development or the difference in the teaching practices (e.g., play-based learning at kindergarten) and the additional difficulty of transition that pupils have to face from kindergarten to primary school.…”
Section: Emotionsmentioning
confidence: 98%
“…However, students' feeling of fear was not strongly observed in this study. On the contrary, [19] found that kindergarten students with special needs view their school future with fear. This difference in the results may stem from the difference in the students' age and development or the difference in the teaching practices (e.g., play-based learning at kindergarten) and the additional difficulty of transition that pupils have to face from kindergarten to primary school.…”
Section: Emotionsmentioning
confidence: 98%
“…Furthermore, teachers worldwide faced difficulties in teaching topics that they considered to be important, and assisting students to gain the skills necessary for the transition to primary education. This issue has been reported in the contexts of Greece, Germany, Turkey, the US and the UK (Quenzer-Alfred et al, 2021;Yildirim, 2021;Gonzàlez et al, 2022;Apostolou, 2022;Wythe, 2022;Bakopoulou, 2022;Gelir, 2023). Finally, preschool teachers have internationally reported on their difficulties to replicate the aspects of traditional education such as inquiry-based teaching when teaching remotely (Timmons et al, 2021), which led them to have doubts on the effectiveness of remote teaching and learning for preschoolers (Atiles et al, 2021;Duran, 2021;Negrette et al, 2022).…”
Section: Teachersmentioning
confidence: 99%
“…(Abdullah, 2020). With a constant threat of infection (Pradana et al, 2020), human life has changed considerably in the social and educational sectors (Lee & Rose, 2021;Quenzer-Alfred et al, 2021).…”
Section: The Effects Of Covid-19 Pandemicmentioning
confidence: 99%